2017
DOI: 10.2989/00306525.2017.1291541
|View full text |Cite
|
Sign up to set email alerts
|

White-backed Vulture Gyps africanus parental care and chick growth rates assessed by camera traps and morphometric measurements

Abstract: Persistent vulture declines across Africa are a cause for concern as the number of species threatened with extinction increases. The White-backed Vulture Gyps africanus was, until recently, considered abundant but has been declining rapidly in recent years due to various threats including decreasing food availability. We used camera traps to investigate nest attendance and food provision at the nests of White-backed Vultures in north-eastern Swaziland. Chick age influenced brooding behaviour of the parents, wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 32 publications
1
1
0
Order By: Relevance
“…After the egg had been laid, the solo breeder was present at the nest for the majority (79%) of the time. The mean incubation duration was 10hrs 40min (standard error [SE] = 115min), similar to that suggested by Mundy et al (1992), but considerably greater than the 5hrs 30min reported by Maphalala & Monadjem (2017). The attendance patterns for this solo breeder showed large variation, ranging from 5mins to a maximum of 3 days, 18hrs 40mins on the nest.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…After the egg had been laid, the solo breeder was present at the nest for the majority (79%) of the time. The mean incubation duration was 10hrs 40min (standard error [SE] = 115min), similar to that suggested by Mundy et al (1992), but considerably greater than the 5hrs 30min reported by Maphalala & Monadjem (2017). The attendance patterns for this solo breeder showed large variation, ranging from 5mins to a maximum of 3 days, 18hrs 40mins on the nest.…”
Section: Resultssupporting
confidence: 83%
“…The attendance patterns for this solo breeder showed large variation, ranging from 5mins to a maximum of 3 days, 18hrs 40mins on the nest. This extraordinary attendance period is much longer than the values reported in either Mundy et al (1992) or Maphalala & Monadjem (2017).…”
Section: Resultsmentioning
confidence: 50%